Determination of antioxidant activity and total phenolic content of Sansevieria roxburghiana (Indian Bowstring Hemp) / Nur Imanie Afifah Ibrahim - Ibrahim, Nur Imanie Afifah (2015)
Many plants have discover their antioxidant potential through several tests such as antioxidant activity, total phenolic compound, and phytochemical screening. Sansevieria roxburghiana is include in the plant that has been antioxidant potential. The objective of this study is to determine the antioxidant activity and total phenolic content of Sansevieria roxburghiana leaves. Leaves of sample was extract using methanolic extract. Antioxidant activity was determined by using DPPH assay, while total phenolic content was measured by using Folin Ciocalteau assay. Data analysis was carried out using one-way ANOYA and Pearson's correlation. Then, antioxidant activity was correlated with total phenolic content. The result shows that Sansevieria roxburghiana leaves has high antioxidant activity and total phenolic content. There is significant result (p < 0.05) for comparison of antioxidant activity between Sansevieria roxburghiana leaves and L-ascorbic acid. The correlation result also shows significant (p < 0.05) and positive good correlation which with r value is 0.916. From this result, it shows that high phenolic compounds of Sansevieria roxburghiana leaves give high antioxidant activity. As conclusion, Sansevieria roxburghiana leaves shows high potential antioxidant from methanolic extract. As conclusion, Sansevieria roxburghiana leaves has high antioxidant potential from methanolic extract. Further studies can continue the determination of antioxidant activity by using several antioxidant assays such as FRAP, ORAC, and ABTS.